Microarray study reveals a transforming growth factor‐β‐dependent mechanism of fibrosis in discoid lupus erythematosus. (1st August 2016) - Solé, C.; Gimenez‐Barcons, M.; Ferrer, B.; Ordi‐Ros, J.; Cortés‐Hernández, J.
Summary: Background: Discoid lupus erythematosus (DLE) is characterized by scarring lesions that develop and perpetuate fibrotic lesions. These are not observed in subacute cutaneous lupus erythematosus (SCLE). The pathophysiological basis of this is currently unknown. Objectives: To identify contradistinctive signalling pathways and cellular signatures between the two type of lupus, with a focus on the molecular mechanisms leading to fibrosis. Methods: We conducted a gene expression microarray analysis in lesional and nonlesional skin biopsy specimens of patients with DLE ( n = 10) and SCLE ( n = 10). Confirmatory reverse‐transcriptase quantitative polymerase chain reaction (RT‐qPCR) and immunohistochemistry were performed on selected transcripts in a new cohort of paraffin‐embedded skin biopsies ( n = 20). Changes over time of a group of selected inflammatory and fibrotic genes were also evaluated in a second biopsy taken 12 weeks later. In vitro functional studies were performed in primary isolated fibroblasts. Results: Compared with nonlesional skin, DLE samples expressed a distinctive T‐cell gene signature. DLE samples displayed a significant CD4 T‐cell enrichment with an imbalance towards T helper 1 cytokine predominance and a relative increased forkhead box (FOX)P3 response. RT‐qPCR and immunochemical analysis over time showed a progressive increment of fibrotic markers and persistent FOXP3 recruitment. Ex vivo upregulation of SERPINE1, MMP9, TGFBR1, phosphorylated SMAD3 and TGFB1 suggested a transforming growth factor (TGF)‐β‐dependent mechanism of fibrosis in DLE, also confirmed by the results observed following in vitro stimulation with TGF‐β. Conclusions: These results highlight major pathogenic pathways in DLE and provide novel molecular targets for the development of new therapies. The data suggest the existence of a TGF‐β‐dependent pathway inducing fibrosis in DLE.